Brazil : forests in the balance : challenges of conservation with development - Lele, Uma J.; World Bank. Operations Evaluation Department (Washington, D.C. : World Bank, 2000)
This review looks at the Bank's projects in the forest sector, projects with forest sector components, and projects with potential impacts on forests, as well as the Bank's non-lending services. These studies seek to judge whether the Bank has 'done the right things' and 'done things right'.
At head of title: World Bank Operations Evaluation Department.
Includes bibliographical references (p. 185-195).
oif 12/08/15
Loan
Keywords: Forest management -- Brazil; Forest conservation -- Brazil; Forests and forestry -- Economic aspects -- Brazil; World Bank